Physicochemical analysis and nutritional properties of fresh, osmo-dehydrated and dried chayote (Sechium edule L.) - Islam, Sahijul; Kumar, Avinash; Dash, Kshirod Kumar; Alom, Saddam (Journal of Postharvest Technology, 2018)
The present study was aimed to investigate the physicochemical, nutritional properties of fresh, osmo-dehydrate and dried chayote. The fresh, osmo dehydrated and dried chayote chayote was analyzed at different conditions, had considerable amount of moisture content, Ash, crude fiber, crude  protein total carbohydrate, total fat, pH, acidity, and ascorbic acid. The important quality parameter as total colour change for fresh, osmo-dehydrated  and dried chayote also investigated. The present observation showed that the both fresh and osmo-dehydrated chayote can be acceptable as good  source of physicochemical and nutritional properties. The oven dried chayote was found to be maximum colour changes and ascorbic acid as  compared to osmo-dehydrated chayote.
Keywords: Osmotic dehydration; chayote; physicochemical; nutritional analysis